Chinese Healthcare Workers’ Knowledge, Attitudes, and Practices in Diabetic Kidney Management: A Multi-Centered Cross-Sectional Study - Duan DF; Wen Y; Yan Y; Li L; Xiao X; Li X; Yan LJ; Ma DY (Dove Medical Press, 2024)
Di-fei Duan,1,* Yue Wen,1,* Yu Yan,1 Ling Li,2 Xiang Xiao,3 Xing Li,1 Lin-Jia Yan,4 Deng-Yan Ma1 1Department of Nephrology, Kidney Research Institute, West China Hospital of Sichuan University /West China School of Nursing, Sichuan University, Chengdu, Sichuan Province, People's Republic of China; 2Department of Nephrology, Kidney Research Institute, West China Hospital of Sichuan University, Chengdu, Sichuan Province, People's Republic of China; 3West China School of Medicine, Sichuan University, Chengdu, Sichuan Province, People's Republic of China; 4The Nethersole School of Nursing Faculty of Medicine, The Chinese University of Hong Kong, Hongkong, People's Republic of China*These authors contributed equally to this workCorrespondence: Deng-Yan Ma, Department of Nephrology, West China Hospital of Sichuan University, No. 37 Guoxuexiang, Wuhou District, Chengdu, Sichuan, People's Republic of China, Email mdy5104@wchscu.cnBackground: Given the importance of diabetic kidney disease (DKD) management, this study aims to explore the knowledge, attitudes, and practices in disease management demonstrated by healthcare workers from the nephrology department.Materials and Methods: This study is a multi-centered cross-sectional study, and adopts snowball sampling, with 530 healthcare workers being recruited to complete a questionnaire covering areas such as demographic characteristics, knowledge, attitude, and practices (KAP) of DKD management. This data was analyzed using descriptive statistics and binary logistics analysis.Results: In this study, 530 healthcare workers were studied, including 94 doctors and 436 nurses. The participants were mainly from general tertiary hospitals in 14 provinces. For Chinese nurse, the results indicate that both poor knowledge level (Odds Ratio (OR) =0.63, 95% Confidence Interval (CI): 0.42- 0.94) and having experience in further medical training in nephrology (OR=1.92, 95% CI: 1.20- 3.08) are associated with the practice levels. For Chinese doctors, having not experience in further medical training in nephrology (OR=0.36, 95% CI: 0.15- 0.83) are associated with their practice levels.Conclusion: In summary, Chinese doctors and nurses in this study showed positive attitudes towards DKD management, but their knowledge and practical skills were lacking. This underscores a notable gap in achieving optimal DKD care. Notably, nurses' knowledge influenced their management practices, and additional nephrology training correlated with better engagement. To improve patient care, enhancing nephrology healthcare professional training and addressing knowledge-practice disparities are recommended.Keywords: knowledge, attitude, practice, diabetic kidney disease